Upaya Peningkatan Kinerja Guru di SMA Negeri 3 Rambang Kuang Kabupaten Ogan Ilir - Andi Fanani; Syarwani Ahmad; Meilia Rosani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to describe and determine efforts to improve teacher performance at State Senior High School 3 Rambang Kuang, Ogan Ilir Regency. Data collection tools used interview methods, documentation, observation and literature review. Data analysis used descriptive qualitative analysis with the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study stated that efforts to improve teacher performance at State Senior High School 3 Rambang Kuang were carried out by planning a performance improvement program, scheduling several activities to improve teacher performance and evaluating the implementation of the performance improvement program based on performance achievement criteria, namely student learning achievement. There are several obstacles in efforts to improve teacher performance both internally and externally such as financial and infrastructure limitations, teacher competence, and stakeholder involvement. The solution to several obstacles faced is by implementing academic supervision and participating in training activities to improve teacher professionalism.